Pembunuhan Sengaja dalam Hadits Riwayat Abu Dawud dan An-Nasa'i (Bulughul Maram No. 1191) dan Pasal 338 KUHP - Putri Yanti Nurhasanah; Tajul Arifin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article explores the concept of intentional murder as addressed in both Islamic law and Indonesian positive law, focusing on the Hadith narrated by Abu Dawud and An-Nasa’i (Bulughul Maram No. 1191) and Article 338 of the Indonesian Penal Code (KUHP). The study examines how intentional murder is viewed and punished in Islam, where the family of the victim has the right to choose between seeking qishash (retaliatory punishment) or accepting diyat (compensation), emphasizing the values of justice, forgiveness, and social harmony. In contrast, the Indonesian Penal Code stipulates a fixed punishment, i.e., imprisonment for up to 15 years, without providing a mechanism for the victim's family to pardon the offender. The article further highlights the differences in these two legal frameworks, underscoring the broader implications of justice and societal peace. Both systems, despite their differences, aim to protect the sanctity of life and ensure that justice is served, while fostering a more just and orderly society. This comparative analysis sheds light on the moral and legal complexities surrounding intentional murder and the varying ways in which justice is pursued in both Islamic and secular legal traditions.